The Structural Properties of Trivalent Rare Earth Ions (Er3+) Doped Borotellurite Glass (Jurnal Teknologi (Sciences & Engineering), 2014)
Six samples of borotellurite glasses with system (80-x)TeO2- 10B2O3 - 10PbO - xEr2O3 (x=0.0, 0.5, 1.0, 1.5, 2.0, 2.5 mol%) have been prepared by using the conventional melt-quenching method. Some basic physical parameters such as density and molar volume were measured. The result reveals that the density and molar volume increases with the increases of mol% of Er2O3. The amorphous nature of the glass has been characterized using X-ray Diffraction (XRD) and all glasses are found to be amorphous in nature. The structure was analysed by FTIR spectroscopy. The FTIR spectra were recorded at room temperature in the frequency range from 650 to 4000Â  cm-1 using Attenuated Total Reflectance (ATR) method. From the IR results, the absorption bands were found to be in the range 667-669 cm-1, 710-712 cm-1, 880-887 cm-1, 981-997 cm-1 and 1190-1204 cm-1 which correspond to the stretching and bending vibrations mode. The absorption peaks around 1386-1388 cm-1 and 3741-3748 cm-1 which ascribed to the hydroxyl-metal bond and hydroxyl-hydrogen bond stretching vibration also have been observed. The FTIR results demonstrate that the existing of erbium in the composition leads to good structural properties thus creating potential for this glass in laser applications.